Early intervention programs for toddlers with Autism Spectrum Disorder: a systematic review - Papaefstathiou, Elpis (2021)
This review identified 8 randomized controlled trials (RCTs) that evaluated early intervention (EI) programs for infants in the age-group 18-48 months who either had been diagnosed with, or were considered at risk for, autism spectrum disorder (ASD). The studies were summarized in terms of participant characteristics, intervention characteristics, rigor of study/research and outcomes. Intervention characteristics included the provision of training to parents. All the studies used RCT design, with control subjects who were either toddlers of typical development (TD) or toddlers with ASD following “treatment as usual” (TAU) or another treatment, and all were rated as strong in terms of quality/rigor.  Positive results were recorded for parental acceptability and satisfaction, and reduction of parenting stress. In most of the studies, the social communication and developmental skills of the toddlers were enhanced. We conclude that EI programs for ASD show promise, and may be beneficial for both the toddlers and the parents, but the limited number of RCTs and the wide variety in intervention programs and assessment instruments used indicates the need for additional research to evaluate the specific benefits.